Criminal justice: the essentials - Lab, Steven P. (Oxford University Press, 2011)
Crime, criminal justice, and policy -- Issues of law -- Policing and law enforcement -- The court system -- Institutional corrections -- Community corrections -- The juvenile justice system -- Criminal justice and discretion